Pengelompokan Data Keluhan Masyarakat Terhadap Fasilitas Umum diKota Binjai Menggunakan Metode Clustering - Dea Syafitri; Yani Maulita; Lina Arlianan Nur Kadim (Jurnal Penelitian Teknologi Informasi dan Sains, 2024)
Public Facilities in Binjai City are infrastructure that is provided free of charge that can be enjoyed by the community and is one of the vacation spots that does not need to spend a lot of money, but there are several infrastructure facilities that are not maintained, dirty and have damage from minor to the most severe, even infrastructure, so that it greatly affects the comfort of the community. In the process of maintaining public facilities in Binjai City in accordance with the Binjai City Regional Regulation Letter Number 1 of 2024 concerning public facilities used for public purposes, including for educational, health, worship, socio-cultural, sports and recreational activities (Hamzah, 2024). The Environmental Service of Binjai City really needs input from the community to continue to help maintain and care for the facilities provided so that the agency can handle and respond to community complaints such as a lot of garbage, dirty, rusty, muddy facilities and others as well as input reported by the community on the cleanliness of public facilities in Binjai City. Therefore, the agency needs a system using the clustering method that can manage community complaint data to be used as information that can assist the agency in taking quick action to deal with the problem of community complaints about public facilities in Binjai City. Based on the research conducted on the case experiment above from testing 20 data, there are 3 groups, namely group 1 there are 5 data and group 2 there are 9 data, and group 3 there are 6 data which can be known that in cluster 2 the group of public complaints about public facilities in Binjai City with public facilities (X) Studion Field, with complaints (Y) Becek, Banyak Sampah, & Berkarat, with Advice (Z) Repair & Maintain Cleanliness.